Double-Modal Locomotion of a Hydrogel Ultra-Soft Magnetic Miniature Robot with Switchable Forms - Shihao Zhong; Zhengyuan Xin; Yaozhen Hou; Yang Li; Hen-Wei Huang; Tao Sun; Qing Shi; Huaping Wang (Cyborg and Bionic Systems, 2024)
Flexible miniature robots are expected to enter difficult-to-reach areas in vivo to carry out targeted operations, attracting widespread attention. However, it is challenging for the existing soft miniature robots to substantially alter their stable shape once the structure is designed. This limitation leads to a fixed motion mode, which subsequently restricts their operating environment. In this study, we designed a biocompatible flexible miniature robot with a variable stable form that is capable of adapting to complex terrain environments through multiple movement modes. Inspired by the reversible stretching reaction of alginate saline gel stimulated by changes in environmental ion concentration, we manufactured a morphologically changeable super-soft hydrogel miniature robot body. According to the stretch and contraction shapes of the flexible hydrogel miniature robot, we designed magnetic fields for swing and rolling motion modes to realize multi-shape movement. The experimental results demonstrate that the deflection angle of the designed flexible miniature robot is reversible and can reach a maximum of 180°. The flexible miniature robot can complete forward swinging in the bar stretch state and tumbling motion in the spherical state. We anticipate that flexible hydrogel miniature robots with multiple morphologies and multimodal motion have great potential for biomedical applications in complex, unstructured, and enclosed living environments.